Democratization of Indian Christianity : perspectives on hegemony, accessibility and resistance - Mocherla, Ashok Kumar; Ponniah, James, 1969- (Abingdon, Oxon : Routledge, 2023)
"This book highlights the transformative potential of democratic Church and Christian community in India. While it invokes the need to democratize Indian Christianity, it explores internal challenges - of caste, class and gender divides - confronting Indian Christianity today. A major contribution to religious studies in India, this book will be of great interest to scholars and researchers of religion, especially in the field of church history, theology, South Asian studies, politics and sociology"--
Modernity, democracy, and Christianity in India / Gnana Patrick, University of Madras -- The Christian churches, democratic developments and people at the margins: case studies from Rajasthan and Odisha / Sarbeswar Sahoo, Indian Institute of Techology (IIT) Delhi & James Ponniah, University of Madras -- Naming the unspoken : domestic violence and the church / Bharathi Nuthalapati, independent researcher.
Keywords: Christianity and politics -- India; Democracy -- Religious aspects -- Christianity; RELIGION / Christianity / General; RELIGION / Christianity / Theology / General